Effect of Titania Addition on the Performance of CoMo/Al2O3 Sour Water Gas Shift Catalysts under Lean Steam to Gas Ratio Conditions - Liu, B; Zong, Q; Edwards, P; Zou, F; Du, X; Jiang, Z; Xiao, T; AlMegren, H (2012)
CoMo/Al 2O 3 sour water gas shift catalysts with and without TiO 2 modification have been tested in parallel industrial reactors under lean steam/gas conditions for two years, and part of catalyst samples was taken out each year during the maintenance period. The catalyst samples have been characterized using temperature programmed sulfurization (TPS), X-ray diffraction (XRD), and laser Raman and BET surface area measurements. The results have shown that adding TiO 2 to the catalyst makes the active components, e.g., Mo and Co, easier to be sulfurized with higher sulfur capacity in the catalyst itself. This may be the main reason why the TiO 2 modified CoMo catalyst to be active even at low H 2S gas stream. The results from industrial operation showed that adding TiO 2 to the shift catalyst increases the catalyst activity and stability, presents the higher shift activity in a broader range of H 2S content, depresses the aggregating of the molybdenum oxide, and reduces carbon deposition. In addition, the TiO 2 additive in the catalyst also helps to maintain the physical properties of the shift catalysts. In the freshly prepared catalyst, the active components e.g., MoO 3 is mainly present in the internal surface or sublayer of the catalyst, but it gradually migrates to the catalyst surface with the time on stream. In summary, the CoMo/Al 2O 3 based sour water gas shift catalyst showed stable shift performance under the lean steam/gas conditions, adding TiO 2 to the catalyst significant improves the catalyst activity and resulting into stable operation in the industrial reactor operation in a wide range of H 2S concentrations. © 2012 American Chemical Society.